Utilización de la taptana para el desarrollo de la inteligencia lógica matemática en el bloque de los números enteros con los estudiantes de 8^vo año en educación básica de la unidad educativa intercultural bilingüe “Monseñor Leonidas Proaño” extensión norte, provincia de Chimborazo, cantón Riobamba, parroquia Lizarzaburu, período septiembre 2015 - enero 2016 - Sayay Minagua, Nina Pacaric (2016)
This research work refers to the use of taptana for mathematical logic intelligence development in the integers unit with students of eight year in basic education of Intercultural Bilingual Education Unit “Monseñor Leonidas Proaño” northern extension, Chimborazo province, Riobamba canton, Lizarzaburu parish, period September 2015 - January 2016. For starting, the referential framework was developed, which consisted of carrying out the research problem, the problem statement, problem formulation, objectives and justification, which sustained the reason of this research. The theoretical framework was developed, in which it was worked on the research variables, which are taptana and mathematical logic intelligence that is supported on scientific documents which base on the research topic. In the methodological framework was established the research design, which was non-experimental, type of research was documentary, field and cross, the level of research was exploratory, the population was five teachers and 23 students, who were surveyed using techniques and data collection instruments. Then, the data surveys were analyzed and interpreted; also, it was conducted complementary activities, which were assessed by observation sheet. Finally the conclusions and recommendations based on the objectives and activities were performed, which took place during the research work, resulting clarify some doubts presented in the investigation and conclude positively.